Housing and respiratory health at older ages. Issue 3 (25th October 2012) - Webb, E; Blane, D; de Vries, Robert
Abstract : Background: A large proportion of the population of England live in substandard housing. Previous research has suggested that poor-quality housing, particularly in terms of cold temperatures, mould, and damp, poses a health risk, particularly for older people. The present study aimed to examine the association between housing conditions and objectively measured respiratory health in a large general population sample of older people in England. Data and methods: Data on housing conditions, respiratory health and relevant covariates were obtained from the second wave of the English Longitudinal Study of Ageing. Multivariate regression methods were used to test the association between contemporary housing conditions and respiratory health while accounting for the potential effect of other factors; including social class, previous life-course housing conditions and childhood respiratory health. Results: Older people who were in fuel poverty or who did not live in a home they owned had significantly worse respiratory health as measured by peak expiratory flow rates. After accounting for covariates, these factors had no effect on any other measures of respiratory health. Self-reported housing problems were not consistently associated with respiratory health. Conclusions: The housing conditions of older people in England, particularly those associated with fuel poverty and living in rented accommodation, may be harmful to some aspects of respiratory health. This has implications for upcoming UK government housing and energy policy decisions.